2018
DOI: 10.1177/0300891618765571
|View full text |Cite
|
Sign up to set email alerts
|

223Ra-chloride therapy in men with hormone-refractory prostate cancer and skeletal metastases: Real-world experience

Abstract: Ra alpha therapy is an important therapeutic option for men with CRPC and symptomatic skeletal metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
5
16
0
1
Order By: Relevance
“…This is in line with literature 16,17 and the results from the ALSYMPCA trial in which anaemia as a serious adverse event was reported in 8% of pts with radium-223 and in 9% of pts treated with placebo 10 . It is also in agreement with real-world experience 18 , and in a study in 92 pts with mCRPC only baseline haemoglobin and ECOG PS were www.nature.com/scientificreports www.nature.com/scientificreports/ significantly correlated with OS among all clinical parameters 19 . For this reason, in our opinion, early identification of pts with sideropenic anaemia in which an oral iron supplement was sufficient to restore haemoglobin levels and improve anaemia is mandatory 20,21 .…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with literature 16,17 and the results from the ALSYMPCA trial in which anaemia as a serious adverse event was reported in 8% of pts with radium-223 and in 9% of pts treated with placebo 10 . It is also in agreement with real-world experience 18 , and in a study in 92 pts with mCRPC only baseline haemoglobin and ECOG PS were www.nature.com/scientificreports www.nature.com/scientificreports/ significantly correlated with OS among all clinical parameters 19 . For this reason, in our opinion, early identification of pts with sideropenic anaemia in which an oral iron supplement was sufficient to restore haemoglobin levels and improve anaemia is mandatory 20,21 .…”
Section: Discussionsupporting
confidence: 89%
“…Recently, a number of real-life studies provided data regarding the safety and activity of radium-223 in clinical practice, outside of trials. 1620 We retrospectively collected data from patients with mCRPC, treated at our institution, to assess the safety and activity of radium-223 in a real-world population. These data represent a source of information useful to define a better treatment strategy and improve clinical outcomes in everyday clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, the cellular uptake of Radionuclide therapy has become increasingly important for the treatment of malignant tumors. Many new radiotherapy agents for the targeted radiotherapy of tumors have been investigated, including 131 I, 21 233 Ra, 22 and 188 Re. 5 Internal radiotherapy is a viable method for the treatment of unresectable HCC.…”
Section: Discussionmentioning
confidence: 99%